Use of Cannabinoids to Treat Acute Respiratory Distress Syndrome and Cytokine Storm Associated with Coronavirus Disease-2019 - Nagarkatti, Prakash; Miranda, Kathryn; Nagarkatti, Mitzi (Frontiers in Pharmacology, 2020)
Coronavirus disease 2019 (COVID-19) is a highly infectious respiratory disease caused by the severe acute respiratory syndrome coronavirus 2. A significant proportion of COVID-19 patients develop Acute Respiratory Distress Syndrome (ARDS) resulting from hyperactivation of the immune system and cytokine storm, which leads to respiratory and multi-organ failure, and death. Currently, there are no effective treatments against hyperimmune syndrome and ARDS. We propose that because immune cells express cannabinoid receptors and their agonists are known to exhibit potent anti-inflammatory activity, targeting cannabinoid receptors, and endocannabinoids deserve intense investigation as a novel approach to treat systemic inflammation, cytokine storm, and ARDS in patients with COVID-19.